Zoledronate interrupts pre-osteoclast-induced angiogenesis via SDF-1/CXCR4 pathway - Mohamed Awad; Elizabeth Taylor-Diaz; Amany Tawfik; Khaled Hussein; Ahmed Elmansi; Mahmoud Elashiry; Ranya Elsayed; Linah Shahoumi; James Borke; William Hill; Fanglong Dong; Mohammed E. Elsalanty (Bone Reports)
Introduction: In this study, we tested the hypothesis that pre-osteoclast signaling is key in triggering post-traumatic angiogenesis in alveolar bone via the SDF-1/CXCR4 pathway. Interruption of osteoclast differentiation through zoledronate (Zol) disrupts the crosstalk between pre-osteoclasts and endothelial cells, hindering the initial angiogenic reaction following dental trauma. This disruption could therefore play a role in the pathogenesis of medication-related osteonecrosis of the jaw (MRONJ). Methods: The effect of zoledronate on the expression of SDF1 was tested in pre-osteoclasts (POC) in vitro. Then, we tested the effect of pre-osteoclast conditioned medium on HUVEC cell differentiation, migration, tube-formation, and CXCR4 expression and activity in-vitro. Lastly, we quantified the effect of zoledronate treatment on post-traumatic vascular perfusion of alveolar bone, using microCT-angiography and immunohistochemistry. Results: SDF-1 mRNA expression decreased in Zol-treated POCs (p = 0.02). Flow-Cytometry analysis showed a decrease in CXCL-12+ (SDF-1α) expressing POCs with Zol treatment (p = 0.0058). On the other hand, CXCR4 mRNA expression was significantly inhibited in Zol-treated HUVECs (p = 0.0063). CXCR4 protein expression and activity showed a corresponding dose-dependent downregulation HUVEC surface treated with conditioned media from POC treated with Zol (p = 0.008 and 0.03, respectively). Similar inhibition was observed of HUVEC migration (p = 0.0012), and tube formation (p < 0.0001), effects that were reversed with SDF-1. Finally, there was a significant reduction of CD31+ HUVECs in Alveolar bone of Zol-treated rats (p = 0.0071), confirmed by significantly lower percentage of blood vessel volume (p = 0.026), and marginally lower vessel number (p = 0.062) in the alveolar bone. Conclusion: Pre-osteoclasts play a crucial role in the initial angiogenic response in alveolar bone following dental extraction. Disruption of this process may be a predisposing factor to osteonecrosis.